Influence of Gender on Perceptions of Barriers to a Police Patrol Career. (September 2020) - Rossler, Michael T.; Rabe-Hemp, Cara E.; Peuterbaugh, Meghan; Scheer, Charles
Policing as an institution has been under immense pressure to increase the representation of women as police patrol officers. As the representation of women in policing has plateaued, increasing research has focused on barriers to women entering patrol work but has not examined the salience of these barriers with respect to males or reliably determined which barriers are most influential to desire to enter a police patrol career prior to employment. Drawing upon survey responses from more than 640 students enrolled in criminal justice courses across five universities (i.e., University of Southern Mississippi, Illinois State University, University of Massachusetts-Lowell, Indiana University-Purdue University Indiana, and Missouri State University), the current inquiry examines the degree to which female and male students differ in their perceptions of barriers to entering a patrol career frequently listed in the literature. The findings indicate that female students view many of these obstacles differently than male students and that these perceptions influence interest in patrol careers.